Feasibility and performance evaluation of different low-tech composter prototypes - Arrigoni, Juan Pablo (2015)
Decentralized composting has become a powerful option for municipal organic waste management. This technology, not only is an effective tool to treat organic waste, producing compost as a valuable by-product, but also represents an innovative way to involve waste generators in treatment operations. Decentralized composting contributes to reducing waste transportation, treatment costs and landfilling volumes thus resulting in a positive impact on municipal waste management programs. In this work, three lowtech composter prototypes were designed and built using discarded metallic oil drums and recycled plastic materials. The composting experience was carried out at an oilfield, using food waste from a catering service for 65 people. Temperature was used as the main indicator of the composting process, and final product quality was characterized through the following variables: total nitrogen, total phosphorous, extractable phosphorous, pH, organic matter and electrical conductivity. Results confirm the effectiveness of this composting technology for organic waste treatment: thermophilic temperatures were reached in all prototypes, and final products obtained from all composters showed high nutrient and organic matter contents, but also high pH and electrical conductivity values, which frequently appear in decentralized composting product; however, obtained values are still adequate for agronomic applications. Nevertheless, some significant differences were found for these variables among the prototypes, possibly related to design characteristics. Finally, composters construction could be optimised by recycling other waste, as shown in this experience (metallic drums, high density polyethylene and accessories), in order to improve the strategies for decentralised composting.